2020
DOI: 10.3899/jrheum.181464
|View full text |Cite
|
Sign up to set email alerts
|

Neurophysiological Features of Peripheral Nervous System Involvement and Immunological Profile of Patients with Primary Sjögren Syndrome

Abstract: Objective The aim of this study was to evaluate: the prevalence, type of neuropathy and the relationship between the presence of autoantibodies and neuropathy development in patients with primary Sjögren syndrome (pSS). Methods 61 pSS patients underwent a complete neurological and electrophysiological examination as well as immunological tests including rheumatoid factor (RF) and autoantibodies as antinuclear antibodies, (ANA), anti-Ro/SSa, anti-La/SSB antibodies. Results The axonal loss or demyelinat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
13
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 13 publications
(16 citation statements)
references
References 29 publications
0
13
0
Order By: Relevance
“…The nervous system is one of the targets of systemic damage in pSS patients ( 6 ). Neurologic manifestations of pSS are diverse, and may involve the peripheral nervous system and/or central nervous system ( 7 ). The coexistence of MG and pSS is limited to reports of one to two cases ( 8 – 21 ).…”
Section: Introductionmentioning
confidence: 99%
“…The nervous system is one of the targets of systemic damage in pSS patients ( 6 ). Neurologic manifestations of pSS are diverse, and may involve the peripheral nervous system and/or central nervous system ( 7 ). The coexistence of MG and pSS is limited to reports of one to two cases ( 8 – 21 ).…”
Section: Introductionmentioning
confidence: 99%
“…Further testing of clinically diagnosed peripheral neuropathy patients revealed that the majority of the test group had sensory neuropathy (8/13, 61%), while a small proportion qualified as both sensory and motor [22]. Conversely, smaller cohorts studies proved significantly increased positivity for anti-Ro/SSA and anti-La/SSB antibodies in pSS patients diagnosed with peripheral neuropathy [23,24]. B-cell proliferation markers were generally higher in PN patients as reported by multiple authors, with a consistent higher incidence of hypergammaglobulinemia in non-PN patients [21,25].…”
Section: Discussionmentioning
confidence: 99%
“…The frequency, prevalence, and diagnostic criteria for peripheral nervous system involvement in SS have been the object of several studies as well as the underlying pathogenetic mechanisms. The reported prevalence of PN varies from 19 to 72% and may represent the first clinical manifestation (61)(62)(63)(64)(65). A cross-sectional study from China in 2018 reported a higher prevalence of PN in sSS than in pSS patients (31.1 vs. 19%) (61).…”
Section: Sjögren's Syndromementioning
confidence: 99%